Data from: Cost, risk, and avoidance of inbreeding in a cooperatively breeding bird - Leedale, Amy; Simeoni, Michelle; Sharp, Stuart; Green, Jonathan; Slate, Jon; Lachlan, Robert; Hatchwell, Ben; Robinson, Elva (Dryad, 2020)
Inbreeding is often avoided in natural populations by passive processes
such as sex-biased dispersal. But, in many social animals, opposite-sexed
adult relatives are spatially clustered, generating a risk of incest and
hence selection for active inbreeding avoidance. Here we show that, in
long-tailed tits (Aegithalos caudatus), a cooperative breeder that risks
inbreeding by living alongside opposite-sex relatives, inbreeding carries
fitness costs and is avoided by active kin discrimination during mate
choice. First, we identified a positive association between heterozygosity
and fitness, indicating that inbreeding is costly. We then compared
relatedness within breeding pairs to that expected under multiple
mate-choice models, finding that pair relatedness is consistent with
avoidance of first-order kin as partners. Finally, we show that the
similarity of vocal cues offers a plausible mechanism for discrimination
against first-order kin during mate choice. Long-tailed tits are known to
discriminate between the calls of close kin and nonkin, and they favor
first-order kin in cooperative contexts, so we conclude that long-tailed
tits use the same kin discrimination rule to avoid inbreeding as they do
to direct help toward kin.